Iludik (2009)
El trabajo de grado expone el diseño de parques infantiles interdisciplinares para la educación preescolar. Estetrabajosedesarrollaapartirdiferentesactividadesfundamentadasdesdelastipologíasdejuego,elentorno,elusuarioysusrelacionesdeusoconobjetoslúdicos,específicamentedirigidosalaedadpreescolar(3a6años),puestoquelascondicionesquerequierenmayorexploraciónnosolofísicassinosensorialesycognitivas, deesteprincipionacelainterdisciplinaridadcomoconcepto),sedanenestaetapa